2020
DOI: 10.1093/scan/nsaa095
|View full text |Cite
|
Sign up to set email alerts
|

Social optimism biases are associated with cortical thickness

Abstract: Optimism biases denote the tendency to see future desirable events as being more likely to happen to oneself than undesirable events. Such biases are important for mental health and may extend to other individuals or social groups (social optimism biases). However, little is known about whether social optimism biases relate to brain structure. Using sparse canonical correlation analysis, we associated cortical thickness (assessed by magnetic resonance imaging) with measures of social and personal optimism bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 71 publications
6
24
1
Order By: Relevance
“…(H2) If this were the case, we assumed that an association would be reflected in both sCCAs, focusing on between‐network functional connectivity (BNFC) and within‐network functional connectivity (WNFC), respectively. (H3) In addition, we hypothesised, that—if such an association existed—it would, like our previous finding on brain structure, point towards a shared neural correlate of both social and personal optimism biases (Moser et al, 2020). (H4) In accordance with the existing literature on optimism and FC, we expected that a neural correlate or optimism would be revealed in both WNFC and BNF and include the SAL, CEN, and DMN (Ran et al, 2017; Wang et al, 2018; Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…(H2) If this were the case, we assumed that an association would be reflected in both sCCAs, focusing on between‐network functional connectivity (BNFC) and within‐network functional connectivity (WNFC), respectively. (H3) In addition, we hypothesised, that—if such an association existed—it would, like our previous finding on brain structure, point towards a shared neural correlate of both social and personal optimism biases (Moser et al, 2020). (H4) In accordance with the existing literature on optimism and FC, we expected that a neural correlate or optimism would be revealed in both WNFC and BNF and include the SAL, CEN, and DMN (Ran et al, 2017; Wang et al, 2018; Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 66%
“…Lastly, it is noteworthy that personal and social optimism biases showed highly overlapping results in that they were situated at similar locations on the sCCA mode's variates in relation to the sCCAs for all RSFC and for BNFC. A previous study that used sCCA to investigate grey matter thickness also found a unified behavioural sCCA dimension that spanned both social and personal optimism (Moser et al, 2020). The present study therefore furthers the notion that the same biological underpinnings are shared between social and personal optimism biases.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Compared with other three quadrants, participants were more willing to sacrifice LW-LC group members in moral dilemmas [ 29 ]. Moreover, desirable events were anticipated to occur significantly more frequently than undesirable events for HW-HC and HW-LC group members while this social optimism biases were reversed for LW-LC groups [ 30 , 31 , 32 ]. Compared to HW-HC and HW-LC groups, the temporoparietal junction and right anterior temporal lobe were recruited when evaluating LW-HC and LW-LC groups, while thinking about LW-LC groups additionally involved the dorsomedial frontal cortex (stereotypical thinking and disgust), inferior frontal cortex (stereotypical thinking), and anterior insula (disgust and repulsion) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%